Adaptation Methods Practiced by Farmers in Response to Perceived Climate Change in Andhra Pradesh - Vijayabhinandana, B.; Asha, R.; Gowtham Kumar, B. S. N. S. (Indian Journal of Extension Education, 2022)
The study was aimed at analyzing adaptation methods practiced by farmers’ and determining factors for adoption to climate change in the Andhra Pradesh (Zone-1 and Zone-6). A cross sectional household survey (by employing structured interview schedule), participant observations and focused PRA were conducted to collect the information on adaptation methods being practiced by 320 randomly selected farmers. The study employed descriptive statistics to types of adaptation measures exercised to cope up with the risk of the change in climate. The study also employed the multinomial logit regression toanalyze the determinants of adaptation method extracted. Factors such as age, education,number of crops cultivated, use of new technology, extension participation, contact and farmer’s commitment are the common determinants for adoption of practices.